Methylglyoxal Impairs GLUT4 Trafficking and Leads to Increased Glucose Uptake in L6 Myoblasts - Engelbrecht, B.; Mattern, Y.; Scheibler, S.; Tschoepe, D.; Gawlowski, T.; Stratmann, B. (Hormone and Metabolic Research, 2014)
Methylglyoxal (MG) is a highly reactive dicarbonyl compound derived mainly from glucose degradation pathways, but also from protein and fatty acid metabolism. MG modifies structure and function of different biomolecules and thus plays an important role in the pathogenesis of diabetic complications. Hyperglycemia-associated accumulation of MG might be associated with generation of oxidative stress and subsequently insulin resistance. Therefore, the effects of MG on insulin signaling and on translocation of glucose transporter 4 (GLUT4) were investigated in the rat skeletal muscle cell line L6-GLUT4myc stably expressing myc-tagged GLUT4. Twenty four-hour MG treatment resulted in elevated GLUT4 presentation on the surface of L6 myoblasts and in an increased uptake of glucose even without insulin stimulation. Exogenously added MG neither effected IRS-1 expression nor IRS-1 phosphorylation. A decreased expression of Akt1 but not Akt2 and concomitantly increased apoptosis were detected following MG treatment. To exclude that oxidative stress caused by MG treatment leads to increased GLUT4 translocation, effects of pretreatment with 2 antioxidants were investigated. The antioxidant and MG scavenger NAC prevented the MG-induced GLUT4 translocation. In contrast, tiron, a well-known antioxidant that does not exert MG-scavenger function, had no impact on MG-induced GLUT4 translocation supporting the hypothesis of a direct effect of MG on GLUT4 trafficking. In conclusion, prolonged treatment with MG augments GLUT4 level on the surface of L6 myoblasts, at least in part through a higher translocation of GLUT4 from the intracellular compartment as well as a reduction of GLUT4 internalization, resulting in increased glucose uptake.
Keywords: diabetes mellitus; insulin; impaired glucose transport; glucose transporter 4; oxidative stress; methylglyoxal